All Days 2016
DOI: 10.2118/179694-ms
|View full text |Cite
|
Sign up to set email alerts
|

Radial and Linear Polymer Flow - Influence on Injectivity

Abstract: Polymer injectivity is a critical parameter for implementation of polymer flood projects. An improved understanding of polymer injectivity is important in order to facilitate an increase in polymer EOR implementation. Typically, injectivity studies are performed using linear core floods. Here we demonstrate that polymer flow in radial and linear models may be significantly different and discuss the concept in theoretical and experimental terms. Linear core floods using partially hydrolyzed polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 24 publications
2
39
0
Order By: Relevance
“…Skauge et al [37] reported that in radial flow, the onset of extensional viscosity occurred at higher shear rates than at typical core flooding. Since radial flow is more representative of real field conditions, results obtained from radial disks should be more accurate as laboratory data for field implementation.…”
Section: Porous Media Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Skauge et al [37] reported that in radial flow, the onset of extensional viscosity occurred at higher shear rates than at typical core flooding. Since radial flow is more representative of real field conditions, results obtained from radial disks should be more accurate as laboratory data for field implementation.…”
Section: Porous Media Propertiesmentioning
confidence: 99%
“…In earlier studies of radial flow experiments, Skauge et al [37] used local pressure taps as a function of radial distance from the injection well to derive in-situ rheology. These experiments demonstrated both shear thinning and strong apparent shear thickening behavior.…”
Section: Polymer In-situ Rheology In Radial Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…History matching approaches of primary and water injection can also impact the prediction of polymer injection. Input variables required to predict polymer flood performance are also part of the uncertainties that needs to be considered in simulation studies (Aldhuwaihi, King & Muggeridge, 2015;Alkhatib, 2015;AlSofi and Blunt, 2011;Chiotoroiu et al, 2016;Fabbri et al, 2015;Romero et al, 2013;Skauge and Salmo, 2015;Skauge et al, 2016;Zhou, Y., Muggeridge, A. H., Berg, C. F., & King, P. R., 2015). Additionally, commercial simulation tools still have some limitations to properly represent the potential formation of in-situ emulsions and its impact on well injectivity/productivity.…”
Section: Summary Discussionmentioning
confidence: 99%
“…Regardless of the nature and differences in the molecular structure of these two polymers, polymer viscosity is the main physical property in the context of polymer flooding. Polymer viscosity depends on polymer molecular structure, molecular weight [3], polymer concentration [4], salinity [5,6], temperature [7,8], degree of hydrolysis [9], pH [10], flow model and type of forces dominating the flow [11].…”
Section: Introductionmentioning
confidence: 99%